Die etiek van termynmarkte - Lotriet, R. A. (Koers, 1995)
The ethics of futures markets Formal futures markets were introduced in South Africa during the beginning of the 1990s. The aim of this article is to investigate the perception that futures markets amount to gambling practices and that they should as such not be tolerated within an economy. Evidence exists of futures markets being banned in countries such as Germany and France because of the belief that these markets foster gambling. The truth in this regard, however, is that futures markets serve as an imperative for the hedging o f price risks by means of futures contracts. Price risks have always been an inherent part o f the free market economy and as such the management of this kind of risk has been making stiff demands on markets in the economy. The manifestation and rapid growth of futures markets in South Africa show that economic needs are thus satisfied. - An important distinction between futures markets and gambling concerns the benefits accruing to society as a whole. It is shown that major differences exist between futures markets and gambling. The proper functioning of a formal futures market is acceptable both on moral and ethical grounds, and thus is also compatible with a Christian philosophy of life.